Periodontitis: etiology, conventional treatments, and emerging bacteriophage and predatory bacteria therapies - Łasica, Anna; Golec, Piotr; Laskus, Agnieszka; Zalewska, Magdalena; Gędaj, Magdalena; Popowska, Magdalena (Frontiers in Microbiology, 2024)
Inflammatory periodontal diseases associated with the accumulation of dental biofilm, such as gingivitis and periodontitis, are very common and pose clinical problems for clinicians and patients. Gingivitis is a mild form of gum disease and when treated quickly and properly is completely reversible. Periodontitis is an advanced and irreversible disease of the periodontium with periods of exacerbations, progressions and remission. Periodontitis is a chronic inflammatory condition that damages the tissues supporting the tooth in its socket, i.e. the gums, periodontal ligaments, root cementum and bone. Periodontal inflammation is most commonly triggered by bacteria present in excessive accumulations of dental plaque (biofilm) on tooth surfaces. This disease is driven by disproportionate host inflammatory immune responses induced by imbalance in the composition of oral bacteria and changes in their metabolic activities. This microbial dysbiosis favors the establishment of inflammatory conditions and ultimately results in the destruction of toothsupporting tissues. Apart microbial shift and host inflammatory response, environmental factors and genetics are also important in etiology In addition to oral tissues destruction, periodontal diseases can also result in significant systemic complications. Conventional methods of periodontal disease treatment (improving oral hygiene, dental biofilm control, mechanical plaque removal, using local or systemic antimicrobial agents) are not fully effective. All this prompts the search for new methods of therapy. Advanced periodontitis with multiple abscesses is often treated with antibiotics, such as amoxicillin, tetracycline, doxycycline, minocycline, clindamycin, or combined therapy of amoxicillin with metronidazole. However, due to the growing problem of antibiotic resistance, treatment does not always achieve the desired therapeutic effect. This review summarizes pathogenesis, current approaches in treatment, limitations of therapy and the current state of research on the possibility of application of bacteriophages and predatory bacteria to combat bacteria responsible for periodontitis. We present the current landscape of potential applications for alternative therapies for periodontitis based on phages and bacteria, and highlight the gaps in existing knowledge that need to be addressed before clinical trials utilizing these therapeutic strategies can be seriously considered.